Post-Operative Wound Infection after Treatment of Open Fracture Type II and Type IIIA by Applying Ilizarov Fixator: A Single Centre Experience in Bangladesh (Bangladesh Journal of Medical Microbiology, 2023)
Background: Treatment of open fracture type II and type IIIA is difficult problem as because there is chance of formation of infection (osteomyelitis) and ultimate nonunion of fracture. Objective: The purpose of the present study was to assess the rate of post-operative wound infection by application of Ilizarov fixator among open fracture of tibia in type II and type IIIA. Methodology: This was a non-randomized clinical trial which was conducted in the Department of Orthopedic Surgery at Ad-Din Sakina Women’s Medical College, Jashore, Bangladesh and at different private institutes in that area from January 2017 to December 2022 for a period of six years. The patients with the age group of 20 to 70 years were selected as study population. Results: A total number of 25 patients were recruited for this study. Out of 25 patients, 20 cases were male and 5 cases were female. Out of 25 patients 3 patients were diabetic and 2 patients were hypertensive. Affected side were on both side. The patients were included in this study and obtained excellent result with ilizarov procedure. Success rate was considered almost 100 present. Three patent developed minor wound infection. Conclusion: In conclusion no wound infection is found among the patients presented with open fracture of type II and type IIIA by application of Ilizarov fixator.Bangladesh Journal of Medical Microbiology, July 2023;17(2):60-65